Lateral flexure of Erebus Ice Tongue due to ocean current forcing and fast ice coupling - Rodrigo Gomez-Fell; Wolfgang Rack; Oliver J. Marsh; Heather Purdie (Journal of Glaciology, 2024)
Ice tongues are unconfined by land on their lateral margins and are sensitive to external forcing from the ocean. They are found sporadically around the Antarctic coast but are common in the western Ross Sea. Lateral flexure creates bending stresses within these ice tongues which is likely to contribute to their fragility and may restrict their spatial distribution. A three-year time series (2017–2020) of synthetic aperture radar interferometry (InSAR) and differential interferometry (DInSAR) is used to observe the lateral flexure of the 10 km long Erebus Ice Tongue as a result of ocean currents. The fast ice area around the ice tongue was mapped during the same period. It was found that when fast ice was absent (34.7% of the time), the average lateral movement of the ice tongue was twice as high (0.44 m) as when it was embedded in fast ice (0.19 m). A significant correlation (0.45) between flexure and tidal currents was found when fast ice was absent. An analytical model tuned to observations suggests that even without sea ice for stabilisation, the lateral bending stresses induced by the ocean are insufficient to cause calving without additional amplifying factors.